The Effect of Module-Assisted Direct Instruction on Problem-Solving Ability Based on Mathematical Resilience - Krida Singgih Kuncoro; Dadang Juandi (Urogram Studi Pendidikan Matematika, Universitas IVET, 2023)
Mathematical resilience is necessary for learning mathematics because the nature and impression of mathematics is a complex subject for most students. This study aimed to determine the effect of the module-assisted Direct Instruction model and mathematical resilience on the problem-solving abilities of prospective teacher students at a private university in Yogyakarta. This research is a quantitative descriptive study with a quasi-experimental design of the nonequivalent control group design type. The sample used was 40 students divided into 19 students in the experimental class, namely the class that received the module-assisted Direct Instruction learning model, and 21 students in the control class, namely the class that received the Expository learning model. The data collection technique is done by giving a mathematical resilience questionnaire. The data analysis technique used quantitative descriptive analysis techniques. The results also show that the Direct Instruction learning model assisted by the module effectively supports problem-solving abilities controlled by the variable of mathematical resilience in discrete mathematics lectures.